Language ability of children with and without a history of stuttering: A longitudinal cohort study. (February 2015) - Watts, Amy; Eadie, Patricia; Block, Susan; Mensah, Fiona; Reilly, Sheena
Abstract Purpose. This study aims to determine whether the communication and language skills of children who have a history of stuttering are different from children who do not have a history of stuttering at ages 2–5 years. Method. This study utilizes data from the Early Language in Victoria Study (ELVS), a longitudinal study with a community sample of 1910 children recruited in Melbourne, Australia, as well as a concurrent study examining the onset and progression of stuttering. Participants with a history of stuttering (n = 181) and a control group without a history of stuttering (n = 1438) were identified according to the established protocol of these two existing studies. Results. The stuttering group scored higher than the non-stuttering group on all of the communication and language outcomes measured. The group differences were statistically significant on four of the seven measures and these findings were maintained when potentially confounding factors were controlled for. Conclusions. Importantly, the children with a history of stuttering, as a group, and the control group without a history of stuttering demonstrated developmentally-appropriate early communication and language skills.